Unidad de formación e integración para la mujer: Plan de renovación estación de la Sabana (2017)
The creation and implementation of the Women's Training and Integration Unit, which aims to support women victims of physical, sexual and psychological abuse through three units: (i) training, training and skills development; Ii) psychological, sexual and medical care; And, iii) legal advice. The proposal not only achieves social inclusion, but also the cultural development of the people who come to UFIM, who will have access to educational and training programs, without neglecting the legal support and health offered.